Lexical tone in Deori: loss, contrast and word based alignment - Mahanta, Shakuntala; Dutta, Indranil; Acharyya, Prarthana (Papers in Historical Phonology, 2017)
In this paper we investigate the existence of tones in Deori, a language which is historically known to have had tonal distinctions. In a study, 5 speakers were recorded for their production of potential lexical tones in a list of 34 words, and a list of 54 monosyllabic roots were recorded for a vowel experiment. We conducted an f0 analysis in order to examine the extent of ‘tonoexodus’ and loss of tonal properties in Deori. To the extent that experimental methods can be used to determine lexical tone, phonetic measurements of f0 and further statistical analysis reliably indicate the distribution of lexically distinct tones. The results show clear presence of tonally distinctive words but without any definitive tonal alignment. We consider the diachrony and synchronic analysis of this and conclude that the syllable is not the Tone Bearing Unit in the conventional sense in current Deori, and that there is no clinching evidence to suggest alignment and spreading of the lexically distinctive tone to the right edge. Given these results, we conclude that tone is spread in the entire word in Deori. We also note that Deori no longer exhibits the prototypical Tibeto-Burman sesquisyllabic pattern and has instead developed an iambic stress pattern.